The structure of acto-myosin - Schröder, Rasmus R. (Myosins, 2020)
After several decades studying different acto-myosin complexes at lower and intermediate resolution - limited by the electron microscope instrumentation available then - recent advances in imaging technology have been crucial for obtaining a number of excellent high-resolution 3D reconstructions from cryo electron microscopy. The resolution level reached now is about 3-4 angstrom, which allows unambiguous model building of filamentous actin on its own as well as that of actin filaments decorated with strongly bound myosin variants. The interface between actin and the myosin motor domain can now be described in detail, and the function of parts of the interface (such as, e.g., the cardiomyopathy loop) can be understood in a mechanistical way. Most recently, reconstructions of actin filaments decorated with different myosins, which show a strongly bound acto-myosin complex also in the presence of the nucleotide ADP, have become available. The comparison of these structures with the nucleotide-free Rigor state provide the first mechanistic description of force sensing. An open question is still the initial interaction of the motor domain of myosin with the actin filament. Such weakly interacting states have so far not been the subject of microscopical studies, even though high-resolution structures would be needed to shed light on the initial steps of phosphate release and power stroke initiation.